2010
DOI: 10.2165/11536690-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Statins and the Reduction of Sudden Cardiac Death

Abstract: Sudden cardiac death is an important cause of cardiovascular mortality with the majority of cases occurring in low-risk groups. HMG-CoA reductase inhibitors (statins) have recently been shown to reduce the incidence of ventricular tachycardia (VT)/fibrillation (VF) and sudden cardiac death, and this has been attributed to their pleiotropic effects. However, it is unclear whether this occurs through an 'indirect' anti-ischemic or 'direct' antiarrhythmic effect. We systematically reviewed articles published on M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 79 publications
0
27
0
4
Order By: Relevance
“…A recent review from Beri et al (2010) has addressed this question by collecting and systematically evaluating data published over a 13-year period on the reduction of VT and VF events, as well as sudden cardiac death in patients suffering from various cardiovascular diseases and treated with statins. They concluded that the anti-arrhythmic/anti-fibrillatory effects of statins most probably result from an anti-ischaemic rather than a direct anti-arrhythmic effect, since a definitive reduction in sudden cardiac death occurred only in patients with ischaemic-type cardiovascular diseases, such as coronary artery disease or ischaemic cardiomyopathy (Beri et al, 2010). These anti-ischaemic effects of statins are supposed to mediate through nitric oxide and can indirectly influence the generation of arrhythmias (Beri et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review from Beri et al (2010) has addressed this question by collecting and systematically evaluating data published over a 13-year period on the reduction of VT and VF events, as well as sudden cardiac death in patients suffering from various cardiovascular diseases and treated with statins. They concluded that the anti-arrhythmic/anti-fibrillatory effects of statins most probably result from an anti-ischaemic rather than a direct anti-arrhythmic effect, since a definitive reduction in sudden cardiac death occurred only in patients with ischaemic-type cardiovascular diseases, such as coronary artery disease or ischaemic cardiomyopathy (Beri et al, 2010). These anti-ischaemic effects of statins are supposed to mediate through nitric oxide and can indirectly influence the generation of arrhythmias (Beri et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the anti-arrhythmic/anti-fibrillatory effects of statins most probably result from an anti-ischaemic rather than a direct anti-arrhythmic effect, since a definitive reduction in sudden cardiac death occurred only in patients with ischaemic-type cardiovascular diseases, such as coronary artery disease or ischaemic cardiomyopathy (Beri et al, 2010). These anti-ischaemic effects of statins are supposed to mediate through nitric oxide and can indirectly influence the generation of arrhythmias (Beri et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12][13] In the past few years, several studies 14 The protective effect of statins on CIN was later verified by the same group in a larger trial (n ¼ 29 409 patients). 15 Preprocedural statin treatment was associated with a lower incidence of CIN (4.37% vs 5.93%, P < .0001) and nephropathy requiring dialysis (0.32% vs 0.49%, P ¼ .03) compared with statin nonuse.…”
Section: Statins and Cinmentioning
confidence: 99%
“…A recent review from Beri et al [105] has addressed this question by collecting and systematically evaluating data published over a 13-year period on the reduction of VT and VF events, as well as sudden cardiac death in patients suffering from various cardiovascular diseases and treated with statins. They concluded that the anti-arrhythmic/anti-fibrillatory effects of statins most probably result from an anti-ischaemic rather than a direct anti-arrhythmic effect, since a definitive reduction in sudden cardiac death occurred only in patients with ischaemic-type cardiovascular diseases, such as coronary artery disease or ischaemic cardiomyopathy [105].…”
Section: The Effect Of Acute Simvastatin Administration On Ischaemia mentioning
confidence: 99%
“…These anti-ischaemic effects of statins are supposed to mediate through nitric oxide and can indirectly influence the generation of arrhythmias [105].…”
Section: The Effect Of Acute Simvastatin Administration On Ischaemia mentioning
confidence: 99%